Bridge to Terabithia - Paterson, Katherine (Crowell, Scholastic, Inc, 1977)
The life of a ten-year-old boy in rural Virginia expands when he becomes friends with a newcomer with whom he builds a fantasy world with, and who teaches him important lessons about life, mortality, and friendship.